![{sin}^{3} \alpha - {cos }^{3} \alpha = {sin}^{3} \alpha - {cos }^{3} \alpha =](https://tex.z-dn.net/?f=+%7Bsin%7D%5E%7B3%7D++%5Calpha++-++%7Bcos+%7D%5E%7B3%7D++%5Calpha++%3D+)
Answers
Answered by
2
Answer:
note : i will use beta in place of alpha.
sin ³ß - cos³ß
= (sinß - cosß)(sin²ß + cos²ß + sinßcosß)
= ( sinß - cosß)( 1 + sinßcosß). ( using , sin² ß + cos²ß = 1).
Answered by
5
Answer:
According to question:-
- hope it helps you...
- please mark it as a brainlist answer....
- also please rate thanks and follow me....
- stay home STAY SAFE...
Similar questions
Social Sciences,
6 months ago
Math,
6 months ago
India Languages,
6 months ago
Physics,
1 year ago
English,
1 year ago
English,
1 year ago
Math,
1 year ago